Rapid determination of lipophilic vitamins in human serum by ultra‐high performance liquid chromatography using a fluorinated column and high‐throughput miniaturized liquid–liquid extraction. Issue 17 (31st July 2017) - Cervinkova, Barbora; Krcmova, Lenka Kujovska; Klabackova, Sava; Solichova, Dagmar; Solich, Petr
Abstract: A high‐throughput miniaturized liquid–liquid extraction procedure followed by a simple ultra‐high performance liquid chromatography method coupled with fluorescence detection for bioanalytical analysis of all tocopherol isomers and retinol in human serum has been developed and validated. In the extraction procedure, a synthetic internal standard tocol was used, which does not occur in the human body. The separation of structurally related vitamins was achieved using a new generation of pentafluorophenyl propyl core–shell stationary phase with elution using methanol and an aqueous solution of ammonium acetate. The fluorescence of retinol and tocopherol isomers was detected at λex = 325, 295 nm and λem = 480, 325 nm, respectively. The rapid baseline separation of all analytes was accomplished within 4.0 min. The sensitivity of method was demonstrated with lower limits of quantification: retinol 0.01 μM, α‐tocopherol 0.38 μM, β‐tocopherol 0.18 μM, γ‐tocopherol 0.14 μM, and δ‐tocopherol 0.01 μM. Possible application of this method in clinical practice was confirmed by the analysis of human serum samples from healthy volunteers. Finally, the simultaneous determination of retinol and all tocopherol isomers in human serum can enable the clarification of their role in metabolism and in diseases such as cancer.